6×(73-65)=2×(45-37)=(35-26)×9=56÷(78-69)=72÷(3+6)=7×(62-54)=(42-36)×5=32÷(4+4)=(75-26)÷7=(5+4)×6=81÷(16-7)=4×(82-75)=(27+21)÷6=45÷(36-27)=3×8÷4=45+7×6=72÷8+26=25+3×7=45÷9×8=63÷9×8=(36+20)÷7=47+32÷8=82-45÷9=68-24÷4=15+54÷9=38+7×4=55-42÷6=89-5×7=5×(25-17)=42+36÷6=56÷8×5=32+5×9=8×(2+7)=27-4×5=(53-21)÷4=(23+31)÷9=36-25÷5=76+2×8=(65-9)÷7=(5+27)÷8=56÷(67-59)=8+2×7=5+56÷7=3+2×9=43-24÷8=(27+54)÷9=42÷(56-49)=(25+24)÷7=5×(36-27)=3+4×9=56-2×8=35+4×6=23+5×6=7×(4+3)=35+5×7=47-28÷7=8+2×7=15-9÷3=7+6×9=49-32÷8=32+56÷8=47-7×5=45÷(3+6)=7×(2+6)=72÷(56-48)=8×(89-80)=2+9×7=9-56÷7=32+4×7=42÷(2+4)=65+8×4=44-25÷5=2×(3+4)=6×(9-7)=56-45÷9=34+5×7=64÷(18-9)=48÷(4+4)=7×(42-37)=8×(3+6)=42-5×7=7+8×4=65-5×3=6+5×7=28÷(37-33)=2×(47-39)=75-3×7=7+6×3=(56+8)÷8=8×(5+3)=36-5×7=82-45÷9=71+2×6=76-5×9=25+36÷4=47-35÷7=4+7×8=9-6÷2=33-4×4=68+4×7=
二年级下册加减乘除混合运算 来自淘豆网m.daumloan.com转载请标明出处.